Interactive Learning Environments for the Educational Improvement of Students With Disabilities in Special Schools - García-Carrión, Rocío; Molina Roldán, Silvia; Roca Campos, Esther (Frontiers in Psychology, 2018)
Providing an inclusive and quality education for all contributes towards the Sustainable Development Goals of the United Nations. High-quality learning environments based on what works in education benefit all students and can be particularly beneficial for children with disabilities. This article contributes to advance knowledge to enhance the quality of education of students with disabilities that are educated in special schools. This research analyses in which ways, if any, interactive learning environments can be developed in special schools and create better learning opportunities for children with disabilities. A case study was conducted with students with disabilities (N=36 and teaching staff in a special school, involving interviews and focus groups. We argue that rethinking the learning context by introducing instruction models based on interaction benefit children with disabilities and provide high-quality learning and safe and supportive relationships for these students, promoting their educational and social inclusion.